2023
DOI: 10.3390/biom13030555
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Cytokines, Growth Factors and Clinical Efficacy between Platelet-Rich Plasma and Autologous Conditioned Serum for Knee Osteoarthritis Management

Abstract: This study aimed to directly compare the contents and the clinical efficacy of the two autologous blood-derived products, platelet-rich plasma (PRP) and autologous conditioned serum (ACS) for osteoarthritis (OA) treatment. The contents of standard-prepared PRP and ACS prepared at 37 °C for 1 h, 3 h, 6 h, and 24 h from healthy volunteers were compared. The clinical efficacy of pain relief in patients with Stage III knee OA was evaluated by a patient-reported visual analog scale (VAS) pain rating. PDGF-BB levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…However, not equaling those achieved by the addition of AMPLEX PLUS. Enrichment with leukocytes [L-PRP] also did not have the desired effects [73]. These attempts, however, did not result in substantial improvement in its efficacy, probably due to the missing supply of some growth factors not present or present in trace amounts in the matrices used.…”
Section: Discussionmentioning
confidence: 99%
“…However, not equaling those achieved by the addition of AMPLEX PLUS. Enrichment with leukocytes [L-PRP] also did not have the desired effects [73]. These attempts, however, did not result in substantial improvement in its efficacy, probably due to the missing supply of some growth factors not present or present in trace amounts in the matrices used.…”
Section: Discussionmentioning
confidence: 99%
“…It is derived from the patient's own blood and is rich in cytokines and growth factors secreted by platelets upon stimulation with glass beads [142]. A crucial step in the preparation is the incubation time, varying anywhere between 1 and 24 h, however a recent study found that incubation for 3 h had the optimal ratio between anti-to pro-inflammatory cytokines, with higher IL-1Ra levels and lower TNFα levels [143]. In addition, levels of IL-1Ra and platelet-derived growth factor (PDGF) were significantly higher in ACS than in platelet-rich plasma (PRP), suggesting better clinical efficacy [143].…”
Section: Knee Osteoarthritis Subtype Representative Moleculesmentioning
confidence: 99%
“…A crucial step in the preparation is the incubation time, varying anywhere between 1 and 24 h, however a recent study found that incubation for 3 h had the optimal ratio between anti-to pro-inflammatory cytokines, with higher IL-1Ra levels and lower TNFα levels [143]. In addition, levels of IL-1Ra and platelet-derived growth factor (PDGF) were significantly higher in ACS than in platelet-rich plasma (PRP), suggesting better clinical efficacy [143]. Other authors compared the efficacy of intra-articular administration of ACS, PRP, hyaluronic acid and GCs and found that both blood-derived products performed better in terms of pain relief and functional improvement without a statistically significant difference between them [144].…”
Section: Knee Osteoarthritis Subtype Representative Moleculesmentioning
confidence: 99%